Electrochemical redox induced rapid uptake/release of Pb(II) ions with high selectivity using a novel porous electroactive HZSM-5@PANI/PSS composite film. (20th August 2018) - Du, Xiao; Zhang, Di; Ma, Xuli; Qiao, Wenlei; Wang, Zhongde; Hao, Xiaogang; Guan, Guoqing
Abstract: A porous electroactive composite based film made of core@shell nanospheres is uniformly fabricated on the conductive substrate by artfully applying the alternative assembly of the polyaniline/polystyrene (PANI/PSS) and the high-crystalline protonated Zeolite Socony Mobil-5 (HZSM-5) nanospheres via a potential pulse method. The isolated HZSM-5 nanospheres are interconnected and linked up by the chains of PANI/PSS that act as bridges for electron transportation. In this composite film, the HZSM-5 nanospheres provide the protons to further improve the electroactivity of PANI based on the unique proton "round-trip" transfer effect during the electrochemical redox process. The obtained HZSM-5@PANI/PSS composite based film shows fast electrochemical uptake/release ability for the removal of Pb 2+ ions from the aqueous solution because of the strong driving force resulting from the electric field, and the adsorption equilibrium time is less than 60 min. When the initial concentration of Pb 2+ ions is 100 mg L −1, the ion adsorption quantity reaches 240.6 mg g −1 and retains 97.1% of its initial value after 5 uptake/release cycles. Especially, the selectivity factors of the HZSM-5@PANI/PSS film for Pb 2+ /Ni 2+, Pb 2+ /Co 2+, Pb 2+ /Cd 2+, and Pb 2+ /Zn 2+ reach up to 21.97, 26.19, 24.61, and 39.29, respectively. Such high selectivities for Pb 2+ ions are realized by artfully using the significantly lower Gibbs energy of dehydration of Pb 2+ ions than that of other listed metal ions, which makes the Pb 2+ ions easily adsorbed into the composite film based on the confinement effect of the HZSM-5. Furthermore, the consumed energy for dehydration is supplied by the electric field, resulting in the decrease of the ions transport resistance and the increase of the adsorption capacity of the composite film. Graphical abstract: Image 1 Highlights: An HZSM-5@PANI/PSS composite film was successfully synthesized. The obtained film showed fast uptake/release ability for the removal of Pb 2+ ions. A high selectivity of the composite film for Pb 2+ ions was realized. The high selectivity was attributed to the confinement effect of HZSM-5.